Respon Varietas Padi Toleran Asam-Asam Organik Pada Sawah Gambut Dengan Pemberian Abu Tandan Kosong Kelapa Sawit - Widodo Haryoko (Fakultas Pertanian Universitas Tamansiswa Padang, 2012)
The experiments have been carried out in the field of peat in Anai Valley sub district, Padang Pariaman district from July to November 2010. The Experiments used factorial design in complete randomized block design. The first factor is 3 tolerant varieties and the second factor is the dose amelioran ie 0, 300, 600 and 900 kg ha-1 with four replications. The results showed that 1) empty fruit bunches of oil palm ash increases growth, 2) increase the yield components, and 3) the highest yield obtained from the three varieties tolerant to the provision of empty fruit bunches of oil palm ash dose of 600 ha-1.